Genus Panthous Stål found from Cambodia, Thailand, and Vietnam, with the redescription of Panthous ruber Hsiao - Truong, Xuan L.; Zhao, Ping; Cai, Wanzhi (Zootaxa, 2006)
The genus Panthous Stål is reported for the first time from Cambodia, Thailand, and Vietnam, and the little known reduviid, Panthous ruber Hsiao, is redescribed and illustrated.